Maximum Power Point Tracking for photovoltaic systemapplied to DC/DC/AC inverter based on Modular Multi‑level Converter structure - Cuong, Tran Hung; Thu Anh, An Thi Hoai (Archives of Electrical Engineering (Online), 2025)
Nowadays, solar power is a potential alternative energy source. To get the best maximum power from solar power, it is necessary to have a strong enough inverter structure and a good control algorithm. This paper presents the Maximum Power Point Tracking (MPPT) algorithm of a solar PV system applied to a DC/DC/AC inverter to obtain maximum power, in which the DC/DC rectifier uses a Boost Converter and the DC/AC inverter uses a Modular Multilevel Converter (MMC). The purpose is to convert electricity from the grid-connected PV system. The MPPT algorithm uses the Incremental Conductance – Integral Regulator (INC-IR) method to find the maximum power point quickly and accurately in different weather conditions. The operation of an MMC uses the Nearest Level Modulation (NLM) method combined with a capacitor voltage balance algorithm to generate maximum AC voltage levels and control the capacitor voltage balance in the MMC. The Nearest Level Modulation method has the advantage of providing a very low valve switching frequency to increase the lifetime of the semiconductor valve. A closed-loop circuit with the PI controller performs the grid-connected power control process. This control and modulation process will produce sinusoidal alternating current (AC) and voltage with a sound total harmonic distortion (THD) index. The simulation of the system will be performed on MATLAB/Simulink software to demonstrate the performance of the proposed method and applied to a 21-level MMC